Langit dan Bumi dalam Struktur Chiastik Naratif Wahyu 20:11-21:1 - Paulus Dimas Prabowo (Sekolah Tinggi Teologi Anugrah Indonesia, 2023)
The hope of believers is fixed on a peaceful future life. But the eternal life in the heavens and the earth to come is only understood as the spiritual realm. Many articles have been written about the future heavens and earth with various approaches. In this article, the author attempts to prove that Revelation 20:11-21:1 is a unit of thought with a chiastic structure that can explain the concept of heaven and earth. The theme contained in the chiastic structure becomes a frame in interpreting the concept of heaven and earth in the text. The method to be used is structural analysis supported by the Freytag pyramid concept and exegetical analysis. The results of the study reveal that heaven and earth in 20:11 is a narrative introduction where the disappearance of heaven and earth describes elements of dramatization and destruction of the white throne judgment, while heaven and earth in 21:1 is a resolution of the narrative, where conflict and tension have been resolved and then created a new state, namely the emergence of a new heaven-earth that is both eternal and materiil. Thus, the church and believers are equipped with an understanding that God's work and eternal life in the world to come are comprehensive, which also touches on materiil aspects. Hope for life in the future is increasingly strengthened through a new, clarified heaven-earth concept. ABSTRAKPengharapan orang percaya tertuju pada kehidupan masa depan yang penuh kedamaian. Namun kehidupan kekal di langit dan bumi yang akan datang hanya dipahami sebagai alam spiritual saja. Banyak tulisan yang diangkat mengenai langit dan bumi yang akan datang dengan beragam pendekatan. Artikel ini penulis berupaya membuktikan bahwa Wahyu 20:11-21:1 merupakan satu unit gagasan dengan struktur chiastik yang dapat menjelaskan konsep langit dan bumi. Tema yang terkandung dalam struktur chiastik menjadi bingkai dalam menafsirkan konsep langit dan bumi dalam teks tersebut. Metode yang akan dipakai adalah analisis struktur yang didukung dengan konsep piramida Freytag dan analisis eksegetik. Hasil penelitian mengungkap bahwa langit dan bumi dalam Wahyu 20:11 merupakan introduksi narasi dimana lenyapnya langit dan bumi mendeskripsikan unsur dramatisasi dan destruksi dari penghakiman tahta putih, sedangkan langit dan bumi dalam 21:1 merupakan resolusi dari narasi, dimana konflik dan ketegangan telah selesai lalu terciptalah keadaan yang baru yakni kemunculan langit-bumi baru yang kekal sekaligus materiil. Dengan demikian, gereja dan orang percaya dibekali dengan pemahaman bahwa karya Tuhan dan kehidupan kekal di dunia yang akan datang bersifat komprehensif, yang juga menyentuh aspek materi. Pengharapan akan hidup di masa mendatang semakin dimantapkan melalui konsep langit-bumi baru yang diperjelas. Kata-kata kunci: langit dan bumi; Wahyu 20:11-21:1; struktur; kiasme; naratif